Inhibitory Effect of Nano-targeted Micelle Administration Combined with in Vitro Radiotherapy on Glioma Based on Nuclear Magnetic Resonance Technology: Nano-targeted Micelle effects on Glioma - Jin, Ronghui; Xu, Yingping; Jiang, Pan (Cellular and Molecular Biology, 2022)
Glioma is a malignant tumor originating from the central nervous system. Glioma is the incidence rate of the central nervous system in adults. Nanotechnology has been widely used in drug delivery in vivo, achieving targeted drug delivery through surface modification. At the same time, the samples measured by NMR have no bias to all compounds, and there is no need for specific internal standards for quantification. Therefore, based on the use of nuclear magnetic resonance technology, this paper analyzed the inhibitory effect of nano-targeted micelles combined with in vitro radiotherapy on glioma. The results show that the coupling constants of β - CH3 of Ala and β - CH3 of Lac are close. It is difficult to distinguish the spectral lines of Ala and Lae by 1.5T NMR. DHA-PLys(s-s)P can efficiently deliver drugs across BBB and into brain parenchymal cells to release drugs. Due to its increased stability in the systemic circulation, DHA-PLys(s-s)P can help to improve drug delivery efficiency. The DNA damage of U87 and U251 cells was more serious than that of C6 cells. There was a positive correlation between DNA damage and Cho/Cr ratio, indicating that nano-targeted micelles combined with in vitro radiotherapy have an inhibitory effect on glioma.